Fostering Sustainable Tourism through Local Leadership and Community Empowerment: The Seruni Mumbul Experience - Amrullah; Muhammad Adi Junaidi; Yogi Birrul Walid Sugandi; Yuliana Safitri; Siti Andriana; Eka Faradila Syahwi (Sumber Belajar Sejahtera, 2026)
Purpose: This study analyzes human resource (HR) capacity-building strategies in the transformation of Denda Seruni Tourism Village, Indonesia. Specifically, it examines how these strategies overcome structural human capital constraints and institutional friction to achieve sustainable rural tourism development. Design/methodology/approach: Grounded in Community-Based Tourism, Transformative Leadership, and Institutional theories, this study employs a qualitative single-case study design. Data were gathered through in-depth interviews (averaging 60 minutes) and participant observation with eight purposively selected informants, including the village head, BUMDes managers, the Pokdarwis chairperson, and five community members. The collected data were analyzed using Miles and Huberman’s interactive model. Findings: The findings reveal that HR capacity development was successfully executed through institution-based training, strategic institutional integration, transformative leadership, and community-based creative economy initiatives. These strategies systematically enhanced community competencies, minimized institutional friction, and contributed 25 percent to Village Original Revenue. However, structural challenges persist, particularly regarding gender-based participation disparities and slow digital technology adoption. Research limitations/implications: This study is limited by its single-site qualitative nature, which may restrict the direct generalizability of the findings to structurally diverse regional contexts. Originality/value: The theoretical novelty lies in conceptualizing a transformative-emancipatory rural leadership model that bridges formal decentralization policies with local human capital enhancement. Moving beyond general economic indicators, this study extends the literature by showing how cohesive synergy between transformative local leadership and institutional alignment serves as a critical boundary condition for sustainable tourism. It offers actionable, practical frameworks for rural destination managers seeking to resolve institutional friction in developing economies.